Seismic and Aseismic Cycle of the Ecuador–Colombia Subduction Zone - Chlieh, M.; Beauval, C.; Yepes, H.; Marinière, J.; Saillard, M.; Audin, L. (Frontiers in Earth Science, 2021)
The Colombia-Ecuador subduction zone is an exceptional natural laboratory to study the seismic cycle associated with large and great subduction earthquakes. Since the great 1906 Mw=8.6 Colombia-Ecuador earthquake, four large Mw>7.5 megathrust earthquakes occurred within the 1906 rupture area, releasing all together a cumulative seismic moment of ~35% of the 1906 seismic moment. We take advantage of newly released seismic catalogs and GPS data at the scale of the Colombia-Ecuador subduction zone to balance the moment deficit that is building up on the megathrust interface during the interseismic period with the seismic and aseismic moments released by transient slip episodes. Assuming a steady-state interseismic loading, we found that the seismic moment released by the 2016 Mw=7.8 Pedernales earthquake is about half of the moment deﬁcit buildup since 1942, suggesting that the Pedernales segment was mature to host that seismic event and its postseismic afterslip. In the aftermath of the 2016 event, the asperities that broke in 1958 and 1979 appears both to be mature to host a large Mw>7.5 earthquakes if they break in two individual seismic events, or a Mw~7.8-8.0 earthquake if they break simultaneously. The analysis of our interseismic coupling map suggests that the great 1906 Colombia-Ecuador earthquake could have ruptured a segment of ~420 km-long bounded by two 50-km wide creeping segments that coincide with the entrance into the subduction of the Carnegie ridge in Ecuador and the Yaquina Graben in Colombia. These creeping segments share similar frictional properties and may both behave as strong seismic barriers able to stop ruptures associated with great events like in 1906. Thinner creeping segments are imaged within the 1906 rupture area and are located at the extremities of the large 1942-1958-1979 and 2016 seismic ruptures. Finally, assuming that the frequency-magnitude distribution of megathrust seismicity follows the Gutenberg-Richter law and considering than 50% of the transient slip on the megathrust is aseismic, we found that the maximum magnitude subduction earthquake that can affect this subduction zone has a moment magnitude equivalent to Mw~8.8 with a return period of 1400 years. No similar event has yet been observed in that region.